Beautiful darkness - Garcia, Kami (Little, Brown and company, 2010)
Ethan Wate used to think of Gatlin as a place where nothing ever changed. Then mysterious newcomer Lena Duchannes revealed a secret world of curses and Supernaturals with terrifying abilities. Lena showed him a Gatlin where impossible, magical, life-altering events happen. Sometimes life-ending. And now that Ethan's eyes have been opened to the darker side of Gatlin, there's no going back. Haunted by strange visions only he can see, Ethan is pulled deeper into his town's tangled history and finds himself caught up in the dangerous network of underground passageways endlessly crisscrossing the South, where nothing is as it seems.